Fundamentals of international financial accounting and reporting - Hussey, Roger (World Scientific, 2011)
Begins with an introduction to accounting and financial reporting, followed by a description of the development of international standards and the present structure, role and operations of the International Accounting Standards Board. This title includes a discussion on individual IFRS (International Financial Reporting Standards)